The T-T pyrimidine (6-4) pyrimidinone UV photoproduct is much less mutagenic in yeast than in Escherichia coli. - Gibbs, P E (1995)
We have examined the mutagenic properties of the T-T pyrimidine (6-4) pyrimidinone UV photoproduct in Saccharomyces cerevisiae, transforming the yeast cells either with single-stranded vectors that carried this adduct at a unique site or with gapped duplex vectors in which the adduct was located within a 28 nt single-stranded region. In an earlier study with SOS-induced Escherichia coli, we found that this photoproduct is highly mutagenic, specifically generating 3' T-->C substitutions in >85% of replicated molecules, and ascribed this specificity to the formation of a stable guanine-pyrimidinone mispair via hydrogen bonds at N-3 and O-2. In contrast, this adduct is very much less mutagenic in yeast, with 60-70% of molecules being replicated accurately and only 12-20% of them exhibiting 3' T-->C substitutions. The enhanced accuracy may reflect the ability of a yeast DNA polymerase, but not E.coli DNA polymerase III, to trap the adduct in a configuration favorable for the formation of an adenine-pyrimidinone base pair.